2020
DOI: 10.1186/s41118-020-00092-5
|View full text |Cite
|
Sign up to set email alerts
|

Decisions on marriage? Couples’ decisions on union transition in Sweden

Abstract: Marriage is an institution that has become optional for many. This study investigates how decisions are taken regarding marriage among Swedish cohabiting couples in the twenty-first century, specifically focusing on whose intentions to marry are most decisive. We use the Young Adult Panel Study conducted in 2009 with augmented register data for 2009–2014 in order to observe both partners’ intentions and to then follow up on which couples ultimately married. The study finds that women’s and men’s intentions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…In addition, factors other than those studied here—children, gender, and gender equality—might be important. For example, the role of marriage is stratified by education and social class (Cherlin, 2020; Duvander & Kridahl, 2020; Jarnkvist, 2019; Pessin, 2018). In Sweden, for instance, those with a tertiary education are more likely than others to marry before childbirth (Holland, 2013) and less likely to remain in cohabitation when they have children (Kennedy & Thomson, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, factors other than those studied here—children, gender, and gender equality—might be important. For example, the role of marriage is stratified by education and social class (Cherlin, 2020; Duvander & Kridahl, 2020; Jarnkvist, 2019; Pessin, 2018). In Sweden, for instance, those with a tertiary education are more likely than others to marry before childbirth (Holland, 2013) and less likely to remain in cohabitation when they have children (Kennedy & Thomson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no empirical study has yet examined whether cohabitants who see marriage as a particularly committed form of union are more or less likely to marry (with the exception of Duvander & Kridahl, 2020, who included this as part of a marriage attitude index). The literature appears to include contradictory arguments.…”
Section: Previous Researchmentioning
confidence: 99%
“…37 Fenomena free sex sebelum menikah sampai dengan perilaku kumpul kebo di luar negeri tentunya mempengaruhi pengambilan keputusan menikah, seperti halnya di Sweden, perilaku free sex dilakukan untuk melihat niat kedua pasangan yang nantinya akan ditindaklanjutkan dalam sebuah janji suci pernikahan. 38 Tentunya tindakan free sex tidak bisa diterapkan di Indonesia, hal ini dikarenakan Indonesia masih sangat kental akan normal agama dan juga nilai susila dan agama. 39 Pemerintah melalui Badan Kependudukan Keluarga Berencana (BKKBN) dan Kementerian Kesehatan (Kemenkes) dalam mengantisipasi hal tersebut, menyelenggarakan sebuah program untuk anak muda, agar anak muda Indonesia mampu merencanakan masa depannya dengan mempromosikan Penundaan Usia Perkawinan (PUP) melalui kegiatan Pelayanan Kesehatan Perduli Remaja (PKPR) dengan mengusung remaja sebagai role model serta sebagai agen perubahan melalui kegiatan Generasi Berencana (Genre) melalui program Jurnal Kesehatan Reproduksi, 14(2), 2023 Pusat Informasi dan Konseling Remaja (PIK-R) yang di tempatkan di sekolah-sekolah.…”
Section: Pembahasanunclassified
“…SES indicators have been associated with marital behavior in the Nordic countries (Duvander & Kridahl, 2020;Sandström & Stanfors, 2020). For instance, high education has been positively linked with the intention to marry among males (Wiik et al, 2010).…”
Section: The Role Of Socioeconomic Statusmentioning
confidence: 99%
“…However, the correlation between income and marital behavior is less clear. On the one hand, there is evidence indicating that in Sweden, income does not play a large role in marriage intentions (Duvander & Kridahl, 2020). However, another study has suggested that income is positively linked with marriage intentio ns among males in Nordic countries (Wiik et al, 2010).…”
Section: The Role Of Socioeconomic Statusmentioning
confidence: 99%